2016
DOI: 10.1038/srep20486
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a caveolin-1 mutant on the function of P-glycoprotein

Abstract: The genetic heterogeneity in cancer cells has an increased chance in the acquisition of new mutant such as drug-resistant phenotype in cancer cells. The phenotype of drug resistance in cancer cells could be evaluated by the number or function of drug transporters on cell membranes, which would lead to decreased intracellular anti-cancer drugs concentration. Caveolae are flask-shaped invaginations on cell membrane that function in membrane trafficking, endocytosis, and as a compartment where receptors and signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…It has also been previously shown that overexpression of caveolin-1 sensitize doxorubicin resistant breast cancer cells by inhibiting P-glycoprotein transport activity [40]. The introduction of K176R mutation on Cav1 led to increased p-gp transport activity in Cav1 overexpressing non-small-cell lung cancer cells [41]. The inverse correlation between Cav1 and p-gp protein levels in ovarian cancer cells may result in enhanced chemo-sensitivity by the inhibition of p-gp protein levels or the activity by Cav1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been previously shown that overexpression of caveolin-1 sensitize doxorubicin resistant breast cancer cells by inhibiting P-glycoprotein transport activity [40]. The introduction of K176R mutation on Cav1 led to increased p-gp transport activity in Cav1 overexpressing non-small-cell lung cancer cells [41]. The inverse correlation between Cav1 and p-gp protein levels in ovarian cancer cells may result in enhanced chemo-sensitivity by the inhibition of p-gp protein levels or the activity by Cav1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent publication, in addition to BBB, P‐gp is expressed in parenchymal central nervous system cells including neurons (Bernstein et al, ). There is also published information available indicating that, in the plasma membrane, P‐gp interacts physically and functionally with caveolin‐1 (Cav‐1), another membrane protein that is important for synaptic signalling, dendritic arborization, and neuronal survival (Lee et al, ). Cav‐1, in turn, regulates the expression of DISC‐1 (disrupted in schizophrenia‐1), long considered a schizophrenia candidate gene, and co‐localizes with DISC‐1 (as it does with P‐gp) in membrane caveolae (Kassan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In A549 and H460 cells, Cav-1 with lysine 176-to-arginine (K176R) mutant fails to form the Cav-1/P-gp complex, thus P-gp functions normally to accelerate the efflux of substrates (i.e., paclitaxel and doxorubicin). Moreover, they also found that Cav-1 K176R mutant could influence Cav-1 oligomerization, which is essential for caveolae structure and is probably the cause for inducing the disassociation of Cav-1 and P-gp [141].…”
Section: Cav-1 and Drug Resistancementioning
confidence: 97%